2015
DOI: 10.1002/jmor.20436
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pairwise shape dissimilarity morphometrics on nonmammalian taxa (Insecta: Neuroptera: Mantispidae)

Abstract: Morphometric dissimilarity metrics aim to quantify the variation between compared specimens such that inferences about their relatedness and alpha taxonomy can be made. Recently, the technique has developed metrics that purport to quantify shape dissimilarity between specimens-employing the use of least squares regression analysis. These metrics have been well applied by studies in the hominin fossil record with an arguably unsubstantiated backing for the technique. Originally postulated was the log10 sem metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…More work is clearly needed to better understand how and why body size varies with geography, if indeed these patterns hold up with more data. In another mantidfly species from Africa, extreme body size variation was reported that appeared to be independent of geography, but this study was limited to a relatively small sample size of only male specimens [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More work is clearly needed to better understand how and why body size varies with geography, if indeed these patterns hold up with more data. In another mantidfly species from Africa, extreme body size variation was reported that appeared to be independent of geography, but this study was limited to a relatively small sample size of only male specimens [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult mantidflies (Neuroptera: Mantispidae) are highly visual and voracious predators with elaborate courtship displays and both sexes can be aggressive or cannibalistic during courtship [ 21 – 23 ]. Regardless of sex, adult mantidflies can vary considerably in size ( figure 1 ) and are therefore an ideal system to use in studying the role of variable SSD on courtship and sexual cannibalism [ 22 , 24 , 25 ]. The intriguing natural history of this system may play a key role in the size variation we observe in adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations